Have Fun while Celebrating IYC—2011 - Mukherjee, Abhas (SCHOOL SCIENCE, 2011)
In the Indian context, the IYC—2011 has significance too. The year 2011 is 150th birth anniversary of Acharya Prafulla Chandra Roy who started the tradition of research in modern chemistry in India and was also instrumental in laying the foundation of chemical industry.